Abatacept treatment for patients with severe acute hepatitis caused by hepatitis B virus infection—Pilot study. Issue 2 (29th November 2020) - Teraoka, Yuji; Imamura, Michio; Uchida, Takuro; Ohya, Kazuki; Morio, Kei; Fujino, Hatsue; Ono, Atsushi; Nakahara, Takashi; Murakami, Eisuke; Yamauchi, Masami; Kawaoka, Tomokazu; Miki, Daiki; et al.
Abstract: Although glucocorticoids have been used for immunosuppression of patients with primary hepatitis B virus (HBV) infection‐induced severe hepatitis, the treatment is associated with a high frequency of adverse events. We conducted a pilot study for evaluating the efficacy and safety of abatacept, a cytotoxic T lymphocyte antigen‐4 immunoglobulin (CTLA4), for acute hepatitis B. Five patients with severe acute hepatitis B (prothrombin activity ≤ 60%) were treated for immunosuppression by abatacept. Four patients received abatacept concurrently with methylprednisolone, and another patient was treated with abatacept alone. Rapid decrease in serum alanine aminotransferase levels, increase in prothrombin activity and improvement of general condition were obtained in four out of five patients. The patient with the most severe hepatitis underwent liver transplantation due to exacerbation of hepatitis in spite of treatment with both abatacept and methylprednisolone. None of the patients developed significant adverse events associated with the use of abatacept. Hepatitis B surface antigen (HBsAg) became negative in all five patients. The effect of abatacept and methylprednisolone for severe hepatitis B was compared using a mouse model. Rapid reduction in mouse serum HBV DNA and human albumin levels and elevation of serum interferon‐gamma and granzyme A levels were observed in HBV‐infected human hepatocyte‐transplanted immunodeficient mice that were administered human peripheral blood mononuclear cells. These hepatocyte injuries were inhibited to a greater extent by abatacept compared to methylprednisolone. Abatacept might be an effective therapy alternative to methylprednisolone to reduce acute massive liver damage for patients with severe acute hepatitis caused by HBV infection.